Similarities and differences between two well-performing healthcare systems: a comparison between the Israeli and the Danish healthcare systems - Daniel Kaminski Rotenberg; Brendon Stewart-Freedman; Jes Søgaard; Shlomo Vinker; Amnon Lahad; Jens Søndergaard (BMC, 2022)
Abstract Background Denmark and Israel both have highly rated and well-performing healthcare systems with marked differences in funding and organization of primary healthcare. Although better population health outcomes are seen in Israel, Denmark has a substantially higher healthcare expenditure. This has caused Danish policy makers to take an interest in Israeli community care organization. Consequently, we aim to provide a more detailed insight into differences between the two countries' healthcare organization and cost, as well as health outcomes. Methods A comparative analysis combining data from OECD, WHO, and official sources. World Health Organization (WHO) and the Organisation for Economic Co-operation and Development (OECD) statistics were used, and national official sources were procured from the two healthcare systems. Literature searches were performed in areas relevant to expenditure and outcome. Data were compared on health care expenditure and selected outcome measures. Expenditure was presented as purchasing power parity and as percentage of gross domestic product, both with and without adjustment for population age, and both including and excluding long-term care expenditure. Results Denmark's healthcare expenditure is higher than Israel's. However, corrected for age and long-term care the difference diminishes. Life expectancy is lower in Denmark than in Israel, and Israel has a significantly better outcome regarding cancer as well as a lower number of Years of Potential Life Lost. Israelis have a healthier lifestyle, in particular a much lower alcohol consumption. Conclusion Attempting to correct for what we deemed to be the most important influencing factors, age and different inclusions of long-term care costs, the Israeli healthcare system still seems to be 25% less expensive, compared to the Danish one, and with better health outcomes. This is not necessarily a function of the Israeli healthcare system but may to a great extent be explained by cultural factors, mainly a much lower Israeli alcohol consumption.